An Examination of Deviant/Adaptive Behaviors in the Organizational Careers of Professionals - Raelin, Joseph A. (Academy of Management Review, 1984)
A model of professional deviant/adaptive career behaviors is presented to clarify the negative behavioral effects experienced by some salaried professionals and proposed as being caused by conflicting expectations with their management. The nature of and precursors to these conflicting expectations are delineated. The cognitive state, attitudes, and specific behaviors, which are the resultants of the expectations, are discussed. Behavioral outcomes are presented in terms of four career elements: management, job, self, and the career. Research and managerial implications are cited.